2020
DOI: 10.1371/journal.pone.0230044
|View full text |Cite
|
Sign up to set email alerts
|

LEFTY2/endometrial bleeding-associated factor up-regulates Na+ Coupled Glucose Transporter SGLT1 expression and Glycogen Accumulation in Endometrial Cancer Cells

Abstract: LEFTY2 (endometrial bleeding associated factor; EBAF or LEFTYA), a cytokine released shortly before menstrual bleeding, is a negative regulator of cell proliferation and tumour growth. LEFTY2 down-regulates Na + /H + exchanger activity with subsequent inhibition of glycolytic flux and lactate production in endometrial cancer cells. Glucose can be utilized not only for glycolysis but also for glycogen formation. Both glycolysis and glycogen formation require cellular glucose uptake which could be accomplished b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 52 publications
(71 reference statements)
0
3
0
Order By: Relevance
“…LEFTY2 upregulates the expression and activity of the glucose transporters sodium-dependent glucose transporter 1 (SGLT1) and GYS1 in Ishikawa and HEC1a cells (two human endometrial cancer cell lines). It facilitates cellular glucose uptake and glycogenesis, although TGF-β1 can diminish this effect in endometrial cancer cells [ 102 ], demonstrating that TGF-β1 negates glycogen synthesis. Glycogen synthase kinase (GSK-3) is a serine/threonine kinase that deactivates the glycogen synthase enzyme and obstructs glycogen synthesis.…”
Section: Tgf-β-dependent Metabolism Of Cancer Cells and Targeted Ther...mentioning
confidence: 99%
“…LEFTY2 upregulates the expression and activity of the glucose transporters sodium-dependent glucose transporter 1 (SGLT1) and GYS1 in Ishikawa and HEC1a cells (two human endometrial cancer cell lines). It facilitates cellular glucose uptake and glycogenesis, although TGF-β1 can diminish this effect in endometrial cancer cells [ 102 ], demonstrating that TGF-β1 negates glycogen synthesis. Glycogen synthase kinase (GSK-3) is a serine/threonine kinase that deactivates the glycogen synthase enzyme and obstructs glycogen synthesis.…”
Section: Tgf-β-dependent Metabolism Of Cancer Cells and Targeted Ther...mentioning
confidence: 99%
“…Furthermore, a recently uncovered pathway involving the circCREBBP-has-miR-1291/LEFTY2 axis was shown to alleviate liver fibrosis [ 48 ]. Moreover, LEFTY2 has been implicated in the pathogenesis and advancement of endometrial cancer [ 49 ]. Nevertheless, this is the pioneering study to suggest LEFTY2 as a potential therapeutic target for PBC.…”
Section: Discussionmentioning
confidence: 99%
“…Among them, SGLT1 and SGLT2, which are encoded by SLC5A1 and SLC5A2, respectively, are GLUT proteins across the cell membrane ( 42 ). Specifically, SLC5A1 has been reported to exert a significant function in various cancer processes, including in pancreatic carcinoma ( 43 ), breast cancer ( 44 , 45 ), gastric cancer ( 46 ), endometrial cancer ( 47 ), etc. In our study, we further confirmed that circ_0003028 could upregulate SLC5A1, and miR-1305 or miR-1322 could downregulate SLC5A1.…”
Section: Discussionmentioning
confidence: 99%